Order Fulfillment in Supply Chain Management: Does the Dimension of Inventory Management Matter in the Aerospace Industry in Malaysia? (Journal of Business Management and Accounting, 2016)
Inventory management is important in meeting customers’ requirements. Similarly, the effectiveness of supply chain management in the order fulfillment process is critical for the organization to stay in business. Inventory determines the service level of any organization as the adequate and timely flow of inventory across the supply chain and manufacturing processes is imperative for the success of the organization. This ensures high rating on order fulfillment and ensures profitability. In the supply chain, inventory management is a critical part of the process as inventory is an asset and any shortage of inventory impact performance negatively. To keep the right level of inventory is a challenge for all companies and the challenge is becoming more complex with the drastic and frequent changes in demand. This also makes the forecasting process  more  tedious  and  difficult.  The  constant  changes  in  customer  preferences with the increases in demand have affected order fulfillment as most manufacturing facilities do not have the additional capacity to cope with sudden increase in orders. They require huge investment and with the shortening of product life cycle, the period to apportion return on investment has to be relatively short compared to the past experience. This affects working capital and increasing working capital is not an easy task unless the organization is wealthy. As Malaysia embarks on the aerospace industry, the dilemma for the manufacturers are similar. The high cost of raw materials in inventory and inventory holding significantly affects order fulfillment. The findings of this study differs from the normal business inventory management practices, thus offering new knowledge and learning curve in the inventory management context of the high technology industry, in particular, the aerospace. The findings indicate that inventory management or the inventory conversion period has an inverse relationship with organization’s profitability.